Peningkatan Kualitas Pelayanan Kyriad Hotel Arra Cepu Melalui Pelatihan Berbasis Kompetensi - Prima Setia Judha Pranatha; Emik Rahayu; Cindy Citya Dima; Rahmanti Asmarani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Kyriad Hotel Arra Cepu is a star-rated hotel located in Blora Regency that plays an important role in supporting tourism activities, business travel, and the development of the local hospitality industry. Despite its strategic position, initial observations and discussions with hotel management revealed several challenges related to service quality, which has not yet fully aligned with current hospitality industry standards. These challenges include limited continuous staff training, inconsistencies between employee competencies and established standard operating procedures, and insufficient professional communication skills. In response, a community service program was developed in the form of competency-based training specifically tailored to the needs of Kyriad Hotel Arra Cepu. The program aims to enhance human resource quality through structured and intensive training aligned with the Indonesian National Work Competency Standards in the hospitality sector, covering Front Office, Housekeeping, Food and Beverage Products, and Food and Beverage Service. The training was implemented using a participatory and hands-on approach supported by ongoing coaching. Training materials included hotel hygiene and sanitation, excellent service practices, telephone operator etiquette, and basic English communication. This program provides direct benefits by improving employee competence, professionalism, and guest satisfaction, while also supporting the implementation of the Tri Dharma of Higher Education and strengthening collaboration between academia and the hotel industry. The expected outcomes include improved staff skills, higher service quality, and a replicable training model for similar hotels.